Strategi Induk dalam Perencanaan Jangka Panjang: Studi Praktik Usaha Pengolahan Kopi di Bangka Belitung - Iren Ajeng; Sipa Aulia; Surya Adi Nugroho; Indah Noviyanti (Pusat Riset dan Inovasi Nasional, 2025)
This study uses a descriptive qualitative approach to understand managerial practices through in-depth interviews, participant observation, and documentation of KopJel One coffee business actors. This study aims to analyze the master strategy applied in long-term planning in coffee businesses in Bangka Belitung. The results of this study indicate that business owners apply a differentiation strategy to increase sales of coffee products, such as through product innovation, quality improvement, and local supplier support. In addition, a key component of their long-term strategy is the implementation of an intense growth strategy through market penetration and product development. This study highlights the importance of a strategy that is in line with the state of the business environment and the company's internal capabilities. The implications of this phenomenon can be a guide for MSME actors in the agricultural sector when they consider business strategies.